2013
DOI: 10.1105/tpc.113.118828
|View full text |Cite
|
Sign up to set email alerts
|

A Genomics Approach to Deciphering Lignin Biosynthesis in Switchgrass

Abstract: It is necessary to overcome recalcitrance of the biomass to saccharification (sugar release) to make switchgrass (Panicum virgatum) economically viable as a feedstock for liquid biofuels. Lignin content correlates negatively with sugar release efficiency in switchgrass, but selecting the right gene candidates for engineering lignin biosynthesis in this tetraploid outcrossing species is not straightforward. To assist this endeavor, we have used an inducible switchgrass cell suspension system for studying lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 103 publications
3
93
1
6
Order By: Relevance
“…In plants that accumulate CGAs, such as tobacco and coffee (Coffea arabica), the enzyme HYDROXYCINNAMOYL-COENZYME A:QUINATE HYDROXYCINNAMOYLTRANSFERASE (HQT) is normally responsible for the formation of CGA from caffeoylCoA and quinic acid, but close HQT orthologs were not found in switchgrass. In contrast, an HCT-like enzyme phylogenetically distant from HCTs or HQTs was discovered from transcriptome analysis of lignifying switchgrass cell suspensions and elongating internodes (Shen et al, 2013) and shown to exhibit HQT activity, preferring quinate instead of shikimate as its acyl acceptor (Escamilla-Treviño et al, 2014). A similar scenario may occur for class II CSEs in lignin biosynthesis.…”
Section: Cse Activity Might Not Be Essential For Lignification In Allmentioning
confidence: 99%
“…In plants that accumulate CGAs, such as tobacco and coffee (Coffea arabica), the enzyme HYDROXYCINNAMOYL-COENZYME A:QUINATE HYDROXYCINNAMOYLTRANSFERASE (HQT) is normally responsible for the formation of CGA from caffeoylCoA and quinic acid, but close HQT orthologs were not found in switchgrass. In contrast, an HCT-like enzyme phylogenetically distant from HCTs or HQTs was discovered from transcriptome analysis of lignifying switchgrass cell suspensions and elongating internodes (Shen et al, 2013) and shown to exhibit HQT activity, preferring quinate instead of shikimate as its acyl acceptor (Escamilla-Treviño et al, 2014). A similar scenario may occur for class II CSEs in lignin biosynthesis.…”
Section: Cse Activity Might Not Be Essential For Lignification In Allmentioning
confidence: 99%
“…Foracomprehensive discussion, the reader is referred to arecent review article. [11] Them ajority of phenylpropanoid genetic strategies have been directed towards ad ecrease in lignin content across plant species,w ith research relating to biomass conversion being targeted at hardwoods, [42][43][44] softwoods, [45] monocots (grasses), [46][47][48][49][50][51][52][53] and dicots (including Arabidopsis and alfalfa/ truncatula). [43, However,a ni ncrease in saccharification yield will not boost the economics of abiorefinery operation if the lignin fraction, at 15-30 wt %o fd ry biomass,b ecomes amore recalcitrant material.…”
Section: Bioengineering Of Ligninsmentioning
confidence: 99%
“…To ensure the successful production of lignocellulosic ethanol, it has been suggested that the elucidation of cell wall-related pathways could provide the means for engineering its structure as well as other bioproducts. In this sense, lignin has garnered special attention due to its potential value-added products, such as plastic and vanillin, and for this reason, many efforts have been made to improve gene annotation of the pathway [102][103][104], molecular phenotyping [105], and metabolic and integrative analysis of plants with altered lignin content [102,[106][107][108]. In an excellent study, comprehensive analysis of 20 Arabidopsis mutants of genes encoding for enzymes of the lignin pathway was accomplished using a systems approach [107].…”
Section: Plant Metabolomicsmentioning
confidence: 99%